PENGARUH TRADITIONAL WORD-OF-MOUTH DAN ELECTRONIC WORD-OF-MOUTH DI INTERNET TERHADAP PROSES KEPUTUSAN PEMBELIAN LAPTOP MEREK ACER PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS TANJUNGPURA PONTIANAK - B11110097, PUTY FEBRIASARI (Jurnal Manajemen Update, 2014)
This research aimed to analyze the influence of word-of-mouth (WOM) for both traditional and electronic towards laptop Acer’s buying decisional process among the students of Fakultas Ekonomi Universitas Tanjungpura Pontianak. This research was designed as an explanatory research. The population of this research is the students of Fakultas Ekonomi Universitas Tanjungpura Pontianak who has buying a laptop Acer and has get information about Acer brand through direct talks with other consumers, or through the website or blog review on the internet. This research was using purposive sampling, then elected a sample size of 100 people. The analysis technique used multiple linier regression analysis by SPSS version 20.0. The results based on multiple linier regression analysis showed that traditional word-of-mouth and electronic word-of-mouth influence significantly to the laptop Acer’s buying decisional process among the students of Fakultas Ekonomi Universitas Tanjungpura Pontianak, with the significance of value 0.000 and R2 of 35.2%, while the rest amounted 64,8% were other factors which are not examined in this study. Keywords : traditional word-of-mouth, electronic word-of-mouth, and buying decisional process